Effects of biobanding on training loads and technical performance of young football players - Jaimar Fellipe Silva de Macedo; Bruno Laerte Lopes Ribeiro; Ayrton Bruno de Morais Ferreira; Ricardo Santos Oliveira; Arnaldo Luis Mortatti (PLoS ONE, 2025)
Background In adolescent sports, grouping by chronological age can advantage athletes born early in the year due to maturation differences. Early maturing athletes often achieve greater performance gains, are perceived as more talented, and receive more specialized training and workloads. This study aimed to assess the effects of biobanding on internal and external training loads, as well as technical performance during small-sided games (SSGs). Methods Twenty male footballers (11.8 ± 1.15 years) participated in this study. Athletes engaged in small-sided games (SSGs) under two conditions: (1) CA–teams formed based on chronological age; and (2) BIO–teams formed based on age relative to peak height velocity (pre-PHV = -2.5 to -1.5, and PHV = -1.5 to -0.5). External load (ETL) was quantified using the PlayerLoad method, while internal load (ITL) was measured using both training impulse (TRIMP) and session-RPE. Player involvement was determined by summing all technical actions performed during the SSGs, with involvement in the game assessed through video analysis of the sessions. Results BIO games significantly increased ETL for pre-PHV (EM = 415.5; 95%CI = 381.5–449.5 a.u.) compared to the CA games (EM = 388.8; 95% CI = 354.8–422.8 a.u.). PHV players had lower ETL (EM = 354.4; 95% CI = 320.4–388.4 a.u.) in BIO compared to CA games (EM = 366.0; 95% CI = 332.0–400.0 a.u.). No significant ITL differences were observed. BIO lowered steals among pre-PHV players vs. CA. Conclusion Biobanded games significantly increased external load (ETL) for pre-PHV players; however, this increase was not substantial enough to affect internal load (as measured by session-RPE and TRIMP) or player involvement.